(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In a constantly changing world, in the dynamics of ongoing social transformations, dehumanization of human life and culture, the question of its full spiritual development is of particular importance. In this regard, a number of urgent problems arise concerning the sphere of education in general, higher education in particular, associated with a change in attitude towards it as a value.